2012
DOI: 10.1111/j.1752-7325.2012.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Using chlorhexidine varnish to prevent early childhood caries in American Indian children

Abstract: Objectives: To test the efficacy of 10% chlorhexidine (CHX) dental varnish applied to the mothers' dentition in preventing caries in American Indian children. Methods: This was a placebo‐controlled, double‐blind, randomized clinical trial. Mother–child pairs were enrolled when the child was 4.5‐6.0 months. Mothers received 4 weekly applications of the study treatment (CHX or placebo) followed by single applications when her child was age 12 and 18 months. Children received caries examinations at enrollment, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Community-based initiatives that rely on community development principles are appropriate (11,12,50). While some clinical trials involving Indigenous children have used chemotherapeutic agents to prevent or arrest caries, they alone do not appear to be the silver bullet (2,51). Rather, multi-pronged approaches that also address determinants of health may offer hope (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Community-based initiatives that rely on community development principles are appropriate (11,12,50). While some clinical trials involving Indigenous children have used chemotherapeutic agents to prevent or arrest caries, they alone do not appear to be the silver bullet (2,51). Rather, multi-pronged approaches that also address determinants of health may offer hope (4).…”
Section: Discussionmentioning
confidence: 99%
“…Potential strategies to consider include motivational interviewing, improving access to early visits, access to fluoridated water and nutritious food choices, along with antimicrobials and applying remineralizing agents to existing caries lesions (4,11,36,47,52). Regardless, we need to find an appropriate metric, like monitoring the volume of children requiring dental surgery, to measure the success of such interventions for these children (2). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of studies focus on the oral health of American Indian children in the continental US (26, 27), there are fewer observational studies and no randomised clinical trials on Alaska Native children. There are 3 possible reasons.…”
Section: Discussionmentioning
confidence: 99%
“…CIPD is the quintessential age‐dependent disease: children are not born with carious teeth, nor are the teeth carious at eruption. Yet in the highest risk children, caries often begins within two years after birth progresses inexorably in severity into cavitation in multiple surfaces and teeth , and continues until affected teeth receive restorations or are extracted. In addition, longitudinal studies have shown that CIPD is also a risk factor for caries in the permanent teeth .…”
Section: Introductionmentioning
confidence: 99%